Analysis Of Palm Oil Waste After Pretreatment Using Environmental Recycling System (Ers) For The Potential Application As Animal Feed - Noor, Nur Farizatul Husna Binti Mohd (Universiti Sains Malaysia, 2020)
The environmental impacts of palm oil mill effluent (POME) have been a concern due to the water pollution and greenhouse gases (GHG) emission. POME is usually released into open-air ponds for remediation, which required longer hydraulic retention time (HRT) and resulting in GHG emissions. Moreover, the abundant of empty fruit bunch (EFB) has been produced and yet has no specific used in large quantity and disposed by incineration method. Thus, this study was conducted to simultaneously treat POME and EFB via Environmental Recycling System (ERS) to convert into value-added product such as animal feed. ERS is an novel innovative method in order to minimize the POME and EFB waste.